Assessing Final Exams for Minimum Learning Competency (MLC) Satisfaction in Seven Ethiopian Primary Schools - Workineh Kebede (Scientia Publica Media, 2025)
This study aimed to assess the quality of teacher-created final exams for Grade Four students in seven government primary schools in Injibara Town, Ethiopia, focusing on their alignment with Minimum Learning Competency (MLC) standards. A qualitative content analysis was conducted on 505 exam items, with two independent raters evaluating their adherence to MLC criteria. The inter-rater reliability, measured using Cohen’s Kappa coefficient, was deemed acceptable. Additionally, a survey was administered to teachers to gauge their awareness of MLC and identify challenges in exam design and administration. Both quantitative and qualitative methods were employed to analyze the data. The results indicated that a substantial portion of the exam items did not meet MLC standards, often failing to evaluate the full spectrum of competencies outlined in the MLC framework. Most questions focused on lower-order cognitive skills, such as knowledge and comprehension, while higher-order cognitive skills and non-cognitive domains like affective and psychomotor competencies were largely overlooked. Open-ended survey responses revealed a lack of clarity among teachers in designing assessments aligned with MLC, insufficient access to resources (e.g., teaching materials, textbooks, sample exams, and digital tools), heavy workloads, and administrative challenges such as tight deadlines, lack of departmental coordination, and insufficient support from school leadership—all of which hindered the design and implementation of competency-based assessments. To address these challenges, the study recommends introducing a Competency-Based Assessment (CBA) course in teacher education programs, providing targeted training on MLC-aligned exam development, recruiting qualified teacher educators, ensuring adequate resources, reducing teacher workloads, strengthening school leadership, and establishing an exam evaluation committee. Further research in this area should also be conducted. These interventions aim to improve assessment quality, enhance teachers’ capacity to design competency-based exams, and advance the implementation of MLC standards in Ethiopian primary schools.